2013
DOI: 10.1177/0300060513475964
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing delayed extubation after infratentorial craniotomy for tumour resection: a prospective cohort study of 800 patients in a Chinese neurosurgical centre

Abstract: Brain stem and lower cranial nerve function were the main factors affecting extubation decision-making. Further research is required, to establish criteria for delayed extubation following infratentorial craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
6
21
0
Order By: Relevance
“…The intention of the present study was to reduce, as much as possible, the ICU stay of patients and the time on mechanical ventilation, and the present results confirm what previous studies reported (11,12,15). In the present study, it was possible to create a similar setting in the two groups of patients regarding hemodynamics, respiratory rate, temperature, SatO 2 , expired CO 2 stability and acid-base balance throughout the surgical event and up to 24 h later.…”
Section: Discussionsupporting
confidence: 87%
“…The intention of the present study was to reduce, as much as possible, the ICU stay of patients and the time on mechanical ventilation, and the present results confirm what previous studies reported (11,12,15). In the present study, it was possible to create a similar setting in the two groups of patients regarding hemodynamics, respiratory rate, temperature, SatO 2 , expired CO 2 stability and acid-base balance throughout the surgical event and up to 24 h later.…”
Section: Discussionsupporting
confidence: 87%
“…The nurse-to-bed ratio was 3∶1. During the study, routine practices of anesthesia and post-operative care were followed, and no attempts were made to change or influence the standard of care [13] .…”
Section: Methodsmentioning
confidence: 99%
“…The neurosurgeon and the ICU physician discuss the patient's status and evaluate the patient by a screen checklist (table 1). 10 When the answers of all items in a checklist are “yes”, the patient is ready for extubation. At this time, a 24 h on-call study coordinator will be informed immediately, and the patient's eligibility for the study is evaluated and confirmed.…”
Section: Methods and Analysismentioning
confidence: 99%